2018
DOI: 10.1159/000495263
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hepatitis C Positive Organs: Patient Attitudes in Urban Chicago

Abstract: Background: Hepatitis C virus (HCV)-infected organs are being transplanted in patients with and without HCV in the direct-acting antiviral era. Little is known about patient attitudes towards receiving an HCV-positive organ. Objectives: The aim of this study is to determine transplant candidates’ attitudes towards receiving HCV-positive organs. Methods: Adult solid organ transplant candidates were identified during a clinic visit or during outpatient hemodialysis from May to December 2017. Willing participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 34 publications
1
40
1
Order By: Relevance
“…In a study of 50 patients awaiting organ transplantation (86% for kidneys), only 60% knew that HCV was a curable disease and only 46% were willing to accept such an organ. Moreover, concerns over HCV curability, insurance coverage, and allograft failure were also expressed . This series, albeit small, underscores the need to expand the knowledge of the impact of the utilization of HCV‐viremic organs in non‐HCV‐viremic kidney recipients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study of 50 patients awaiting organ transplantation (86% for kidneys), only 60% knew that HCV was a curable disease and only 46% were willing to accept such an organ. Moreover, concerns over HCV curability, insurance coverage, and allograft failure were also expressed . This series, albeit small, underscores the need to expand the knowledge of the impact of the utilization of HCV‐viremic organs in non‐HCV‐viremic kidney recipients.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, concerns over HCV curability, insurance coverage, and allograft failure were also expressed. (28) This series, albeit small, underscores the need to expand the knowledge of the impact of the utilization of HCV-viremic organs in non-HCV-viremic kidney recipients. The same issue applies to those awaiting LT, and studies addressing access to treatment and cost of HCV treatment in this population are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to our ndings, these studies found that older patients and white patients were more willing to accept HCV-infected kidneys than younger and black patients, respectively. [13,14] The reason for the contrast in the results is unclear but may represent unmeasured differences in each transplant center's characteristics and patient population.…”
Section: Discussionmentioning
confidence: 96%
“…Given that HCV D + /R − LT is already occurring, ensuring its fairness nationwide and justice for patients in need of LT is paramount. LT providers need to ensure that providing HCV D + /R − LT does not disadvantage patients or communities who may have been misinformed or have outdated information about HCV pathology and treatment after LT. One recent patient survey study showed that African Americans were less likely than whites to accept an HCV + kidney graft . Although it is unclear whether this attitude extends to liver grafts, further studies are needed to determine whether disparities exist in beliefs toward HCV D + /R − LT.…”
Section: Justicementioning
confidence: 99%
“…LT providers need to ensure that providing HCV D + /R − LT does not disadvantage patients or communities who may have been misinformed or have outdated information about HCV pathology and treatment after LT. One recent patient survey study showed that African Americans were less likely than whites to accept an HCV + kidney graft. 27 Although it is unclear whether this attitude extends to liver grafts, further studies are needed to determine whether disparities exist in beliefs toward HCV D + /R − LT. Furthermore, to promote equity in liver graft allocation, transplant centers that do not provide HCV D + /R − LT should inform their patients that other transplant centers may be performing HCV D + /R − LT.…”
Section: Utilitymentioning
confidence: 99%